AB0590 A SINGLE CENTER RETROSPECTIVE ANALYSIS OF EFFICACY AND SAFETY BETWEEN LOW-DOSE VERSUS HIGH-DOSE RITUXIMAB AS REMISSION INDUCTION THERAPY IN JAPANESE PATIENTS WITH ANCA-ASSOCIATED VASCULITIS. (June 2019) - Hirose, Kei; Hirata, Manami; Yamamura, Yuriko; Ueno, Akiko; Yamamura, Masahiro
Abstract : Background: Administration of four once-weekly doses of 375 mg/m 2 rituximab (RTX) has been indicated for ANCA-associated vasculitis (AAV) as remission induction therapy. However, randomized controlled trial for Japanese AAV patients have never been conducted, although Japanese AAV patients are characterized by the predominance of elderly patients with microscopic polyangiitis (MPA). Objectives: To compare the efficacy and safety between low-dose versus high-dose RTX therapy as remission induction therapy in Japanese patients with AAV. Methods: A single center retrospective analysis of 27 consecutive AAV patients with RTX therapy was performed. Clinical and laboratory variables at diagnosis, rates of complete remission (CR), defined as Birmingham Vasculitis Activity Score (BVAS)=0 and prednisone <7.5 mg/day, adverse effects, and vasculitis relapses following RTX use. Results: Twenty-five MPA patients and 2 GPA patients (14 males and 13 females) were included in the present study. Twenty-six patients were positive for MPO-ANCA. Their median age was 77 years (range: 40-85 years). Treatments were determined according to the discretion of the attending physician. As remission induction therapy, 18 patients were treated with once or twice (1/2) RTX infusions (375 mg/m 2 ), while 9 patients with 3 or 4 times (3/4) RTX infusions. At 6 months, 55.6% of the 1/2 infusion group (10/18) and 44.4% of the 3/4 infusion group (4/9) reached CR. At 6 months, mean PSL levels were 7.8 mg/day in the 1/2 infusion group and 6.6 mg/day in the 3/4 infusion group. At 18 months, 88.9% of the 1/2 infusion group (16/18) and 77.8% of the 3/4 infusion group (7/9) were survived. 0% of the 1/2 infusion group (0/18) and 33.3% of the 3/4 infusion group (3/9) were relapsed. Severe adverse effects occurred in 38.9% of the 1/2 infusion group (7/18) and in 22.2% of the 3/4 infusion group (2/9). Conclusion: Our retrospective analysis indicated that cumulative CR rates and PSL tapering did not significantly differ between low-dose versus high-dose RTX as remission induction therapy in Japanese AAV patients, mostly elderly MPA patients, although there was no significant difference in severe adverse effects such as opportunistic infections between them. Disclosure of Interests: None declared